The Influence of Content Marketing and Influencer Collaboration on Brand Awareness and Customer Engagement: A Case Study on Hovè Modest Fashion - Muna, Shofi Nilal; Arifin, Zaenal; Ratna, Raden Roro (Universitas KH. Abdul Chalim Mojokerto, 2025)
Hovè is a local modest fashion brand with a minimalist, elegant, and timeless concept, targeting urban women aged 20–35. Since its establishment, the business has relied mainly on digital channels such as Instagram, Shopee, and TikTok Shop for marketing and sales, while also experimenting with offline sales through boutique partnerships. The business implementation includes market and competitor analysis, differentiation strategy based on timeless design and strong brand storytelling, limited-scale production, and promotion through content marketing and influencer collaboration. Nevertheless, Hovè faces several challenges. Brand awareness remains relatively low, sales fluctuate sharply with months of no transactions, limited capital constrains both production capacity and promotional efforts, and customer engagement is still suboptimal. These issues are reflected in financial performance, where most months record losses due to high variable costs and inconsistent revenue. To address these problems, Hovè adopted a digital marketing optimization strategy using the AIDA model, developed lifestyle, storytelling, and product highlight content, and strengthened influencer collaborations to expand reach and enhance consumer engagement. Evaluation results indicate that KOL collaboration is most effective in raising awareness, while product highlight content contributes more strongly to conversion. In conclusion, Hovè shows potential for sustainable growth provided it can maintain consistent digital content management, reinforce influencer strategies, diversify sales channels, and improve financial and operational efficiency.